Entre a história e o turismo: as cidades e seu patrimônio cultural (Nova Hartz-RS) - Priamo, Vania Inês Avila (Universidade do Vale do Rio dos Sinos, 2013)
The present essay explores the theme of cultural heritage in the cities, approaching it as Nova Hartz county and assuming it as examples for the discussion about the same material heritage from the county represented by the historic buildings and the immaterial, represented by the food and by the parties, resulted of different migratory movements that gave to the county the current historic cultural resignation. The discussion is tangible by the concepts of memory and representation. Instruments, like the education for the heritage, the protective legislation and tourism are essential for the preservation of these assets that are related to the ways of being and live of the residents of cities and their linked representations. This study is based in bibliographic researches, field research and in oral sources to understand what the community comprehends to be its inheritance, as well as its relationship with it through events that get along intramural of the city and others characterized as extramural.
Keywords: Patrimônio cultural; Memória; Imigração; Cidade; Representação; Cultural heritage; Memory; Immigration; City; Representation; ACCNPQ::Ciências Humanas::História